2019
DOI: 10.1186/s12884-019-2232-8
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and validation of a model predicting the likelihood of vaginal birth following labour induction

Abstract: Background There is high-quality evidence supporting induction of labour (IOL) for a number of maternal and fetal indications. However, one fifth of inductions fail to result in vaginal births, requiring cesarean deliveries. This has negative clinical, emotional and resource implications. The importance of predicting the success of labour induction to enable shared decision-making has been recognized, but existing models are limited in scope and generalizability. Our objective was to derive and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 30 publications
1
22
0
5
Order By: Relevance
“…In addition, three trials investigated patient reported outcomes such as satisfaction and comfort. Fifth, the included studies, used a one-size-fits-all approach to labour induction, comparing a predetermined method in each arm, regardless of the cervical status, uterine activity, parity and other patient characteristics that are could influence the effectiveness and safety of labour induction [25][26][27]. Ideally, the method of choice for cervical ripening or labour induction should consider these parameters, and individualize care, to ensure the highest possible chance of a vaginal birth, with the lowest risk of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, three trials investigated patient reported outcomes such as satisfaction and comfort. Fifth, the included studies, used a one-size-fits-all approach to labour induction, comparing a predetermined method in each arm, regardless of the cervical status, uterine activity, parity and other patient characteristics that are could influence the effectiveness and safety of labour induction [25][26][27]. Ideally, the method of choice for cervical ripening or labour induction should consider these parameters, and individualize care, to ensure the highest possible chance of a vaginal birth, with the lowest risk of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The candidate predictor variables had to be easily accessible through characteristics' data. To identify predictor variables, a systematic review of the literature was conducted [8][9][10][11][12][14][15][16]. The following variables were recorded: maternal age, height, weight, baseline body mass index (BMI), weight change during pregnancy, gestational age at delivery, premature rupture of membranes (PROM), epidural analgesia, meconium-stained amniotic uid, induction methods(oxytocin, amniotomy, disposable cervical dilator balloon, prostaglandin(Propess or Misoprostol)), neonatal sex, and neonatal birth weight.…”
Section: Characteristicsmentioning
confidence: 99%
“…Currently, several published models studied on prediction of cesarean delivery were mostly focused on the white populations [8][9][10][11][12], whereas the data of the majority of Han ethnic backgrounds of the Chinese population are insu cient. To date, China lacks the relevant researches, and there is limited empirical evidence and clinical experience reported.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes spontaneous vaginal delivery doesn't go so well, resulting in pregnancies have to undergo the emergency operation. And yet, maternal and perinatal complications are higher when a failed trial of labor results in an emergency cesarean delivery [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several published models studied on prediction of cesarean delivery were mostly focused on the white populations [7,[11][12][13][14], whereas the data of the majority of Han ethnic backgrounds of the Chinese population are insu cient. To date, China lacks the relevant researches, and there is limited empirical evidence and clinical experience reported.…”
Section: Introductionmentioning
confidence: 99%